Coaching jako efektywna koncepcja i metoda podnoszenia sprawności zarządzania, na przykładzie zawodowych grup kolarskich - Witkowski, Kazimierz; Cieśliński, Wojciech (Coaching as an effective conception and method of advancing competent management on the example of professional cycling teams, 2005)
A model of developmental transformation of sport organizations, including the use of coaching, was presented in the paper. It was indicated that among concepts of mastering and development of organizations - not necessarily of the sport nature - original conceptions of sport and business coaching may be applied as a factor implementing efficiency of management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 391-396